The beam transport system for the Small Quantum Systems instrument at the European XFEL: optical layout and first commissioning results. (3rd February 2023) - Mazza, Tommaso; Baumann, Thomas M.; Boll, Rebecca; De Fanis, Alberto; Grychtol, Patrik; Ilchen, Markus; Montaño, Jacobo; Music, Valerija; Ovcharenko, Yevheniy; Rennhack, Nils; Rivas, Daniel E.; Rörig, Aljoscha; et al.
Abstract : The soft X‐ray beam from the SASE3 source at the European XFEL is delivered to the SQS instrument by a beam transport system. The system layout and performances are reported. Abstract : The Small Quantum Systems instrument is one of the six operating instruments of the European XFEL, dedicated to the atomic, molecular and cluster physics communities. The instrument started its user operation at the end of 2018 after a commissioning phase. The design and characterization of the beam transport system are described here. The X‐ray optical components of the beamline are detailed, and the beamline performances, transmission and focusing capabilities are reported. It is shown that the X‐ray beam can be effectively focused as predicted by ray‐tracing simulations. The impact of non‐ideal X‐ray source conditions on the focusing performances is discussed.